Clinical outcome and component-specific antibody levels in egg allergic children after lightened oral immunotherapy - Koffert, Anna (Doyma, 2025)
Objective: To evaluate the clinical outcome of lightened version of egg oral immunotherapy (OIT) and to analyze egg allergen component-specific antibody levels during short up-dosing with egg white powder and maintenance by egg in daily diet.
​​​​​​​
Patients and methods: Eighteen egg-allergic children received egg powder with short updosing and they maintained tolerance using egg in daily diet. Seventeen egg-allergic children served as a control group. Component-resolved analysis of serum immunoglobulin E (IgE), IgA1, IgA2, and IgG4 levels was determined at inclusion, after up-dosing, and after 1 year of immunotherapy. Skin-prick tests were performed at inclusion and after 1 year of therapy.
Results: All 18 patients in the egg OIT group were successfully desensitized. Desensitization was achieved on average in 4.5 months. In the control group, only two children tolerated egg in oral food challenge after 1 year. Of the measured immune markers, smaller wheal diameters in skin-prick testing, reduction in component-specific IgE levels, and increase in compo-nent-specific IgA1, IgA2, and IgG4 levels were associated with desensitization.
Conclusion: A lightened egg OIT is effective and safe in children with egg allergy. Increase in all egg component-specific IgA1, IgA2 and IgG4 levels and decrease in all egg componentspecific IgE levels were observed after 12 months of OIT.